Performance assessment of madrasah ibtidaiyah jamilurrahman and madrasah ibtidaiyah islamic center bin baz teachers in customer service in 2025/2026: Predictive validative comparison - Widiyanto; Sumarno; Nemer Alotaibi; Musthafa Ahyar Muttaqin; Dendi Fitriansyah; Muzhaffar Aiman Rabbani Muzhaffar Aiman Rabbani (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze and compare the Organizational Citizenship Behavior (OCB) of teachers in customer service at Madrasah Ibtidaiyah (MI) Jamilurrahman and MI Islamic Centre Bin Baz (ICBB) in Bantul Regency, DIY. The extra behavior of the teacher's role is considered crucial to maintain the quality of educational services in the midst of fierce competition, which will ultimately affect customer satisfaction (parents/guardians of students) and the sustainability of the institution. The approach used is quantitative descriptive. Data were collected using a Likert scale questionnaire (1-5) that measured five dimensions of extra-role behaviors (Altruism, Conscientiousness, Sportsmanship, Courtesy, and Civic Virtue). The sample used is the population, namely all teachers of MI Jamilurrahman (N=24) and MI ICBB (N=29) for the 2025/2026 school year. Data were analyzed using descriptive statistics (mean, median, mode). The results of the analysis showed that the extra behavior of teachers' roles in the two madrasas was in the category of High to Very High. The average score (Mean) of the extra behavior of the role of MI Jamilurrahman teacher is 67.77 (Very High Category), while MI ICBB is 65.62 (High Category). Overall, the extra behavior of the role of MI Jamilurrahman teachers is slightly superior (+2.15) to MI ICBB. MI Jamilurrahman's superiority is also seen in each dimension of extra role behavior: Altruism (+0.19), Conscientiousness (+1.15), Sportsmanship (+0.06), Courtesy (+0.15), and Civic Virtue (+0.60). This difference indicates that MI Jamilurrahman teachers have slightly higher potential for initiative, volunteerism, and dedication beyond formal duties, likely supported by a more collaborative and supportive organizational climate.